2023
DOI: 10.1002/mds.29622
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Transcranial Ultrasound Neuromodulation in Parkinson's Disease: A Pilot Study

Nardin Samuel,
Mandy Yi Rong Ding,
Can Sarica
et al.

Abstract: ObjectiveLow‐intensity transcranial focused ultrasound (TUS) is a novel method for neuromodulation. We aimed to study the feasibility of stimulating the bilateral primary motor cortices (M1) with accelerated theta‐burst TUS (a‐tbTUS) on neurophysiologic and clinical outcomes in Parkinson's disease (PD).MethodsPatients were randomly assigned to receive active or sham a‐tbTUS for the first visit and the alternate condition on the second visit, at least 10 days apart. a‐tbTUS was administered in three consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 29 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…A recent advancement in the field demonstrated the safety of an accelerated theta burst protocol (a-tbTUS) in PD patients, involving three consecutive TUS sessions separated by 30-min intervals. While our pilot study confirmed the safety of a-tbTUS and observed changes in motor cortical excitability, clinical improvements, as assessed by the UPDRS score, did not reach statistical significance [ 127 , 128 ].…”
Section: Transcranial Ultrasound Stimulationmentioning
confidence: 81%
“…A recent advancement in the field demonstrated the safety of an accelerated theta burst protocol (a-tbTUS) in PD patients, involving three consecutive TUS sessions separated by 30-min intervals. While our pilot study confirmed the safety of a-tbTUS and observed changes in motor cortical excitability, clinical improvements, as assessed by the UPDRS score, did not reach statistical significance [ 127 , 128 ].…”
Section: Transcranial Ultrasound Stimulationmentioning
confidence: 81%
“…The Institutional Review Board at Virginia Tech approved all experimental procedures (IRB #21-796). N=16 healthy participants (25.7 years ± 3.4 years; range (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34); M/F 5/11), who met all inclusion/exclusion criteria provided written informed consent to all aspects of the study.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%
“…LIFU has been extensively studied in small [3][4][5] and large animals [6][7][8][9] including humans [10][11][12][13]. It has been demonstrated to produce safe [14,15] and reversible inhibition and excitation [8,16] in different parts of the cortex [12,13,17] and subcortical structures [1,18] including emerging clinical applications [19][20][21][22][23]. An additional promising clinical application for LIFU is pain as demonstrated in both primates [8,24] and humans [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…This approach enhanced both motor and cognitive functions, along with increased perfusion at the substantia nigra. In another study, Samuel et al (2023) [71] delivered in stroke treatments, utilizing NIBS such as repetitive TMS (rTMS) and transcranial direct current stimulation (tDCS) to normalize interhemispheric imbalances in stroke patients. In the case of tFUS, although not a study involving stroke patients, Ren et al (2023) [25] (listed in Table 2) observed that the excitatory effects of tFUS stimulation on the unilateral M1 in humans were accompanied by decreased excitability in the contralateral M1, suggesting the potential of tFUS in clinical interventions such as a rebalancing modality of the interhemispheric imbalances in stroke.…”
Section: Alzheimer's Disease (Ad) and Parkinson's Diseasementioning
confidence: 99%
“…Furthermore, the interhemispheric inhibition (IHI) hypothesis is a concept of neurophysiological mechanism in which one hemisphere, when excited, inhibits the activity of the other, playing a role in the regulation of motor functions. The IHI hypothesis has been employed as an effective strategy [21] TMS hotspot Zeng K et al 2022 [26] TMS hotspot Samuel N et al 2022 [27] TMS hotspot Samuel N et al 2023 [71] TMS hotspot Shamli Oghli Y et al 2023 [33] TMS hotspot Thync Inc.…”
Section: Strokementioning
confidence: 99%